Valoração do petróleo da bacia do recôncavo baiano: um estudo comparativo - Barros, Wagram Emídio de (2005)
The national production of oil is predominantly offshore and of heavy oil with high texts of contaminantes. The Bahian Recôncavo has a production of light oil Shore with peculiar characteristics, adjusted to the lubricant production and paraffin of excellent properties to be used as substance cousin for petrochemical. The bahian production is gotten from mature fields differently of the production offshore of Rio de Janeiro and, its economic viability is of great importance for the local development. Inside of the methodology, used for the National Agency of Petroleum (ANP) for the calculation of the governmental participation, it was defined as reference the used minimum prices as Would carry n.º 206, of 29 of August of 2000, that it differentiates the cuts of oil in: it has led; medium and weighed, without taking in account the easiness of refining of this oil and the final destination of its cuts. This is a criterion uniform that can be generating distortions in the evaluation of the oils of different national origins.This dissertation presents an analysis of the prices of the oils produced in the basin of recôncavo bahian, searching to evaluate of comparative form if its valuation is compatible with its intrinsic value in function of its quality, comparative adequacy to the park of refining of the e region advantages with relation to the too much national and imported oils. It is considered, then, an alteration of the methodology of calculation for the valuation of the bahian oil, introducing parcels that value the specific fractions destined the production of specialties such as paraffins and lubricant as well as factors of logistic and specification of contaminants. It was verified that becoming fulfilled this alteration, the final valuation of the bahian oil is greater that the calculated one for the current method. This addition of value favors the producers of this region, when of venda of the product and as consequence promotes a rise in the collection of the governmental participation.